Мідний кований казан ранньоскіфського часу з округи Більського городища - Шрамко, І.Б. (Археологія, 2023)
У статті вперше в науковий обіг уведено дані про
випадкову знахідку мідного тонкостінного казана
в заплаві р. Стара Ворскла, у найближчій окрузі
Більського городища. На підставі морфологічного
та рентгено-флуоресцентного аналізу предмета
показано його місце серед інших нечисленних по-
дібних знахідок на території Лісостепової Скіфії,
простежено зв'язок із центральнокавказькими виробничими центрами, а також вплив урартського
мистецтва в оформленні ручок. Попередньо виріб
віднесено до першої половини VI ст. до н. е. Рідкісний артефакт міг потрапити на лівий берег Дніпра
з кочовиками, які просувались до Українського лісостепу через Кавказ. In the article, for the first time, data on the accidental discovery of a thin-walled copper cauldron in the floodplain of the Stara
Vorskla River (Left Bank Dnipro Forest-Steppe), in the nearest district of Bilsk fortified hillfort, are introduced into scientific
circulation. On the basis of morphological and X-ray fluorescence analyses of the object, its place among other few similar finds
in the territory of Forest-Steppe Scythia is shown, the connection with the Central Caucasian production centers, as well as the
influence of Urartian art in the design of handles, are traced. Previously, the item was assigned to the first half of the 6th century
BC. The rare artefact could have reached the left bank of the Dnipro with the nomads advancing to the Ukrainian forest-steppe
through the Caucasus.
The cauldron found differs in appearance from other similar artefacts and hasn’t had any exact analogues yet. However, the
high rims and the probable presence of a low pallet may indicate a production tradition of Caucasian craftsmen. At the same
time, the design of the figured overlays for fastening the handles in the shape of a stylised bird with spread wings definitely points
to the Urartian (East Asian) cultural tradition. The technique of making cauldron attachments, with a perpendicularly placed,
separately cast ring, used by Urartian foundries is indicative, which, at first glance, could suggest an Urartian import. Clarity is
provided by the results of spectral analyses. According to the elemental composition of the metal, each of the three cauldrons
known today with similar handle attachments, found in the territories of the Ukrainian forest-steppe, has a copper body and
bronze handles with a significant content of lead (from 10 to 15%), which indicates the possibility of their manufacture in workshops,
located on the southern slopes of the Caucasus Mountains, where at the end of the 8th—6th centuries BC there was a large
centre for the production of various types of metal utensils. In our case, the attachments on the cauldrons were cast according to
the local recipe, but based on Urartian prototypes.
Based on the archaeological context and the results of RFA analyses of the metal of thin-walled cauldrons of the Early
Scythian period, found in the territory of Forest-Steppe Scythia (Bilsk, Repiakhuvata Mohyla and Kruhlyk), it can be concluded
that all of them were made in the first half of the 6th century BC in one of the Central Caucasian production centres by order
and according to the taste of the nomadic elite. The possibility of Urartian craftsmen working in one of these production centres
cannot be eliminated.